Utilization of Pineapple as Essential Oil for Respiratory Disorders: Case Study - Permana, Roni; Afiyatusyifa, Fidya; Dewi, Riska Yuliana (Universitas Mandiri, 2025)
This study aims to examine the effectiveness of pineapple (Ananas comosus) Essential oil in alleviating mild respiratory disorders such as cough and shortness of breath. A quasi-experimental method was used, involving two groups: an experimental group receiving therapy with pineapple Essential oil and a control group receiving warm water without oil. The results showed a significant reduction in respiratory symptoms in the experimental group (p < 0.01), while no significant change was observed in the control group. The bromelain content and volatile compounds in pineapple play a role in reducing inflammation and helping to open the airways. These findings indicate that pineapple Essential oil has potential as a natural alternative therapy for mild respiratory problems.